Efficacy and Safety of apatinib in patients with intermediate/advanced hepatocellular carcinoma: A prospective observation study - Yu, Wen-Chang (Medicine (Baltimore), 2018)
This prospective study aimed to evaluate the efficacy and safety of apatinib in patients with intermediate/advanced hepatocellular carcinoma (HCC). The patients with intermediate/advanced HCC, who met predetermined inclusion and exclusion criteria, underwent oral treatment of apatinib 500 mg daily. The drug-related adverse effects were monitored by regular follow-up and workup including laboratory tests and imaging examinations. Tumor response was assessed by response evaluation criteria in solid tumor criteria. The time to tumor progression (TTP) and overall survival rate (OS) were calculated using the Kaplan–Meier method. A total of 31 patients were enrolled in the study from October 28, 2015 to December 28, 2016. The number of patients with intermediate and advanced HCC was 4 (12.90%) and 27 (87.10%), respectively. The mean tumor size was 9.47 ± 5.48 cm (range: 1.2–19 cm). Vascular invasion was seen in 14 patients (45.16%). A total of 21 (67.74%) patients exhibited extrahepatic metastases. On the basis of first follow-up computed tomography and magnetic resonance imaging at 6 weeks after treatment, 10 (32.26%), 15 (48.39%), and 6 (19.35%) of 31 patients achieved a partial response, stable disease, and progression of disease, respectively. Response rate and disease control rate were 32.26% and 80.65%, respectively. The median TTP was 4.8 months (95% confidence interval: 3.75–5.86 months). Furthermore, 6- and 12-month OS rates were 73.8% and 55.4%, respectively. Grade 3 thrombocytopenia (6.45%) and hypertension (48.39%) were the most common hematologic and nonhematologic toxicities. Grade 3 elevation of either serum total bilirubin or aminotransferase (6.45%) was observed as the top incidence among important indexes of liver function. Our preliminary findings suggest apatinib is a safe and effective therapy in intermediate/advanced HCC patients with high tumor response and survival rates.